Study on Routing Protocols for Delay Tolerant Mobile Networks. (10th January 2013) - Gong, Haigang; Yu, Lingfei
Delay tolerant mobile networks feature with intermittent connectivity, huge transmission delay, nodal mobility, and so forth. There is usually no end-to-end path in the networks and it poses great challenges for routing in DTMNs. In this paper, the architecture of DTMNs is introduced at first, including the characteristics of DTMNs, routing challenges, and metric and mobility models. And then, the state-of-the-art routing protocols for DTMNs are discussed and analyzed. Routing strategies are classified into three categories: nonknowledge-based approach, knowledge-based approach, and social-based approach. Finally, some research issues about DTMNs are presented.